FAKTOR – FAKTOR YANG MEMPENGARUHI PAJAK REKLAME DI KOTA SEMARANG (Students' Journal of Accounting and Banking, 2012)
Advertisement Tax represent is one of Regional Tax revenue which necessary for the Semarang City. This matter was proven during the fiscal year 1985-2010 income of Advertisement Tax revenues was increased. However in its development during the years 1985-2010, the percentage growth of Advertisement Tax revenues have fluctuated. The purpose of this study was to analysis the influence of Total Population, Per Capita Gross Regional Domestic Product and Number of Industry of Advertisement Tax receipts in the Semarang City.The Results of this study is expected to give some benefit and input for the Local Government of Semarang, particularly the Office of Financial Management Regions. Simultaneously test results indicate that overall independent variables (Total Population, GDP and Tota lindustry) together can show its influence on Advertisement Tax revenue. R-squared value for 0,421 amounted to 42,1 percent which means the Advertisement Tax revenue variation can be explained from variations of the three independent variables. While the rest that is equal to1,7percent is explained by another cause sout side the model. The results showed that the three variables, all of them have positive and significant influence on advertisement tax revenue in the Semarang City. Keywords: Total Population, GDP, Number of Industry, Advertisement Tax, Semarang City.